A methodological analysis of blockchain-based smart contracts in international trade - Bhat, Asif; Mohd Nor, Rizal; Amiruzzaman, Md; Islam, Md Rajibul (2022)
When trustworthy computing is necessary, several applications use blockchain. Trade finance is one of these fields that might greatly benefit from a decentralized method of conducting transactions. This study gives the first evaluation of Accepire-BT, a software platform designed for the practice of collaborative Trade Finance. Smart contracts enforce the suggested solution using Solidity, the core programming language of the Ethereum blockchain. Remix and MetaMask were used to assess the performance of the Rinkeby test network. Per cycle, smart contracts need less than one minute, according to the findings of the early test. Also included is a discussion of the fees associated with using the public Ethereum Rinkeby network.